BIOAKUMULASI LOGAM Pb DAN Cr DALAM SISTEM BIOFILTRASI VERTIKAL DENGAN INOKULUM BAKTERI YANG DIISOLASI DARI BEBERAPA PERAIRAN KAWASAN DENPASAR SELATAN - Imanniar, Dini; Suyasa, I.W. Budiarsa; Sudiarta, I. W. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Research of bioaccumulation of Pb and Cr in vertical biofiltration systems with bacterial inoculum derived from aquatic sediments South Denpasar aims to get the best sediment sources that can be used as an active suspension to process metals Pb and Cr dissolved. Sediment samples taken from some waters are ecosystems Mangrove Statue Ngurah Rai Tuban, Benoa Harbour and Estuary Dam Suwung. Each sediment samples were grown in a liquid medium to get the best active suspension, which was determined by an increase in biomass ( VSS ) and the speed of growth. Best active suspension is used as inoculum in the vertical biofilters to decreaseconcentration of Pb and Cr dissolved. Ability of vertical biofilter is determined by their effectiveness in lowering levels of Pb and Cr and capacity of the system used. The results showed that the vertical biofiltration system capable of lowering the concentration of Pb and Cr to each concentration became 0.1680 ppm and 0.1460 ppm within 6 hours of treatment with initial concentration of 2 ppm respectively. The results showed that the vertical biofiltration system capable of decreasing the concentration of Pb and Cr became 0.1680 ppm and 0.1460 ppm within 6 hours of treatment with initial concentration of 2 ppm respectively. This concentration has been below the qualitystandard (PerGub Bali No.8 Tahun 2007). The highest effectiveness of vertical biofilters system against Pb and Cr occurred while processing time of 24 hours with the respective value amounted to 99.49 % and 99.41 %. While the value of biofiltration capacity in lowering the concentration of Pb and Cr amounting 4,3188x10-3 mg/g and 4,5369x10-3 mg/g. In microbiological tests, one type of bacteria that play a role in the process of bioaccumulation of Pb and Cr is Bacillus sp in the amount of 20 CFU/g.
Keywords: Bifiltration, active suspension, effectiveness, capacity